Rancang Bangun Sistem Kontrol Starter Berbasis IoT (Internet of Things) - Kurnia Paranita Kartika Riyanti; Balok Hariadi (Universitas Darul Ulum, 2022)
Today's automotive industry is experiencing rapid development triggering many new innovations involving Internet of Things (IoT) technology. By utilizing IoT (Internet Of Things) in the vehicle starter system, it will certainly save time, especially when heating the vehicle before use. We can do an internet-based starter for 5 minutes before using our vehicle so it is very beneficial for people who have high mobility. The automatic starter system can run according to its function by utilizing the wifi network which is controlled using the Blynk application with a simple electrical circuit using the appropriate microcontroller. This system works by pressing a button on social media, but our response will be forwarded in the form of an order that will be received and then instructs the actuator to start the vehicle. Over time, the system can get better and simpler for the future, such as turning on the vehicle's air conditioner automatically or for using other systems.